First maternal uniparental disomy for chromosome 2 with PREPL novel frameshift mutation of congenital myasthenic syndrome 22 in an infant - Ping Zhang; Bingbing Wu; Yulan Lu; Qi Ni; Renchao Liu; Wenhao Zhou; Huijun Wang (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Congenital myasthenic syndrome 22 (CMS22) is a rare autosomal recessive disorder due to isolated PREPL deficiency and characterized by neonatal hypotonia, muscular weakness, and feeding difficulties. Eight such cases have already been reported, while maternal uniparental disomy with a PREPL pathogenic mutation has never been involved. Methods Trio whole‐exome sequencing (WES), comparative genomic hybridization microarray (arry‐CGH), and Sanger sequencing were performed on a 6‐month‐old girl with severe neonatal hypotonia and feeding difficulties. Also, the phenotype and genotype of reported CMS22 patients were reviewed. Results In this female infant, we identified a novel homozygous frameshift mutation in PREPL (c.1282_1285delTTTG, p.Phe428Argfs*18) by trio‐WES. Sanger sequencing confirmed that her mother was heterozygous and her father was normal. Trio‐WES data showed that 96.70% (1668/1725) variants on chromosome 2 were homozygous and maternally inherited, suggesting maternal uniparental disomy of chromosome 2 [UPD(2)mat]. Array‐CGH did not show copy number variants (CNVs) but revealed complete UPD(2). Conclusion To date, nine patients with CMS22 have been reported including our patient, and we report the youngest and the first UPD(2)mat with PREPL novel homozygous pathogenic mutation case, which expand the mutation spectrum of PREPL gene.